2009
DOI: 10.1063/1.3131426
|View full text |Cite
|
Sign up to set email alerts
|

Bioeffective Ultrasound at Very Low Doses: Reversible Manipulation of Neuronal Cell Morphology and Function in Vitro

Abstract: Direct and safe manipulation of neurons by external means is an increasingly studied therapeutic modality with the potential to treat many neurological diseases. Anticipating such future applications, we investigated reversible bioeffects of very low dose focused ultrasound on neuronal cell morphology and function in vitro. To test morphological changes, undifferentiated PC12 cells were serum-cultured. The culture plates were placed on an inverted optical microscope. An f/1.1 ultrasound transducer with a water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
(17 reference statements)
3
17
0
Order By: Relevance
“…Optical microscopy of insonified cultured cells (PC12 cells from the rat adrenal gland) confirms this and demonstrates reversible distortion [2]. These observations are consistent with the early work of Wood [3] and more recent studies by Haake [4] and Lee [5] and their coworkers.…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…Optical microscopy of insonified cultured cells (PC12 cells from the rat adrenal gland) confirms this and demonstrates reversible distortion [2]. These observations are consistent with the early work of Wood [3] and more recent studies by Haake [4] and Lee [5] and their coworkers.…”
Section: Introductionsupporting
confidence: 81%
“…Full experimental details were presented previously [2,10] and are summarized here. Hippocampal slices were obtained from 8-day old Sprague Dawley rats and cultured for 6 days [2]. The in vitro cultures were exposed to multiple 100-ms 4.04-MHz ultrasound pulses from a 42-mm diameter, 90-mm spherical cap transducer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of hyperthermia treatments, for example, it has been suggested that multi-focal ultrasound distributions would result in a more uniform temperature field, which could be more finely controlled and quicker to create [1][2][3]. In ultrasonic neuro-modulation, an emerging application of FUS [4][5][6][7][8][9], multi-focal ultrasonic distributions may also be used for patterned simultaneous stimulation, inhibition or modulation of neural structures and populations, much as multi-focal light distributions are already being applied for parallel photostimulation [10][11][12][13]. In contrast to visible light, FUS is not heavily scattered or absorbed when penetrating biological tissues and may be applied completely non-invasively to various neural structures including cortical areas and even deep-seated nuclei [9].…”
Section: Introductionmentioning
confidence: 99%